The human soul (jivatma) and its ultimate goal (moksa) in the context of Taittiriya Upanisad (3.10.5): a study in an aspect of Hindu eschatology - Saradananda, Swami (Rhodes University, Faculty of Divinity, Department of Divinity, 1995)
This research was stimulated by pastoral concerns regarding the high rate of suicide in the South African Hindu community. On the one hand it was found that traumatized individuals contemplating suicide were woefully ill-equipped with helpful religious guidelines and on the other it is known that the primary and authoritative scriptures of Hinduism possess a wealth of information that can promote healing. This work uses the Taittiriya Upanishad (3.10.5) to address this challenge. The early Vedic writings are not systematized nor are they fully explicable except through commentaries. This research surveys the early Vedic and Upanisadic Writings in order to show the literary, social and philosophical conditions under which the texts were produced. The Taittiriya Upanisad is the culminating part of several strands of thought that emerged from the earlier Taittiriya School. In order to interpret the text of this Upanisad it was necessary to link its key concepts with other Upanisads of this period. Further interpretations emerged from later Upanisads. These texts were viewed in the light of several commentators - Shaukara (medieval period), and Vivekananda, Aurobindo and Radhakrishuan of the Neo-Vedanta movements. In the early Vedic period the soul is a metaphysical entity. Upon death it is judged and in accordance with its good or bad actions, heavenly rewards or the punishments of hell are meted out to it. Heaven and hell are final eschatological goals for the soul in the Vedic period. In the later Vedic or Upanisadic period it is found that heaven and hell are temporary eschatological goals. The ultimate goal becomes Liberation which implies the cessation of duality and the realization of non-duality. Correspondingly the Taittiriya Upauisad defines the soul in a manner in which its components have the potential to achieve this later goal. Here the soul is a formulation of five sheaths: body, vital energy, mind, intellect and bliss with an immortal consciousness as its focus. Functioning under the effects of ignorance each sheath binds the soul to suffering and rebiiths either on earth or on other planes (heaven or hell). However, each sheath also possesses an intrinsic capacity to liberate the soul from suffering. Tills work explores these negative and positive capabilities of the sheaths and points out the path by which the soul's divine potential may be realized. The ultimate healing or liberation occurs when the 'focus-consciousness' of the soul is intuitively realized. This consciousness is one with the universal consciousness. This achievement produces the 'liberated soul' who experiences ecstasy at this knowledge of oneness. This research also points out that the Neo-Vedanta movements, unlike their medieval counterparts, have a life-affirming and positive social attitude that seeks to draw from ancient texts for the purposes of healing and social upliftment.
Keywords: Upanishads -- History and criticism; Hindu eschatology; Soul -- Hinduism; Suicide -- Religious aspects -- Hinduism